Prospective 3D analysis of facial soft tissue augmentation with calcium hydroxylapatite. (4th July 2017) - Simunovic, Filip; Schlager, Stefan; Montanari, Michaela; Iblher, Niklas
ABSTRACT: Background : Facial rejuvenation is an expanding field with an increasing number of treatment modalities. Several non-autologous filler materials are available for soft tissue augmentation. Calcium hydroxylapatite (CaOH) is aimed at increasing collagen neosynthesis and thereby producing long-term augmentation effects. Despite a multitude of observational reports, the field is suffering from lack of quantitative morphometric evaluation methods.Objective : The objective of this proof-of-principle study was to investigate whether the effects of facial tissue augmentation with CaOH (RADIESSE™) can be quantified and followed up using 3D surface scanning.Methods : 3 female subjects received augmentation of the mid and lower face with CaOH. The faces were recorded prior, directly after, and two weeks and six months after the injection using standardized photos and 3D scanning. Computational analysis allowed quantifying the change in volume and displacement of the facial surface. Additionally, a patient satisfaction questionnaire was administered.Results : In all subjects, increase in facial volume could be quantified and was present after two weeks and six months.Conclusions : 3D surface scanning is an adequate tool for objective quantification of changes after facial augmentation with filler materials. Persistent volume augmentation after CaOH injections could be quantified after two weeks and six months. Evidence level: IV.